Functional Near-Infrared Spectroscopy Neurofeedback Enhances Human Spatial Memory - Hou, Xin; Xiao, Xiang; Gong, Yilong; Li, Zheng; Chen, Antao; Zhu, Chaozhe (Frontiers in Human Neuroscience, 2021)
Spatial memory is an important cognitive function for human daily life and will be dysfunction or decline in elderly life or clinical diseases. Functional near-infrared spectroscopy neurofeedback (fNIRS-NFB) is a promising neuromodulation technique with several special advantages that can be used to improve human cognitive functions by changing the neural activity of targeted brain regions or networks. In this pilot study, we intended to test the feasibility of fNIRS-NFB to enhance human spatial memory ability. The lateral parietal cortex, an accessible cortical region in the posterior medial hippocampal-cortical network that plays a crucial role in human spatial memory processing, was selected as the potential feedback target. A placebo-controlled fNIRS-NFB experiment was conducted to instruct individuals to up-regulate the neural activity in this region or an irrelevant control region. Experimental results showed that individuals learned to regulate the neural activity in the region of interest successfully. A significant increase in spatial memory performance was found after 8-session neurofeedback training in the experimental group but not in the control group. Furthermore, neurofeedback-induced neural activation increase correlated with spatial memory improvement. In summary, this study preliminarily demonstrated the feasibility of fNIRS-NFB to improve human spatial memory and has important implications for further applications.